Analisis Variabel Penilaian Pegawai Berdedikasi Tinggi Dan Dampaknya Terhadap Kinerja Pegawai Pada Dinas Penanaman Modal Dan Pelayanan Terpadu Satu Pintu Kabupaten Sleman - T. Martina Oktadiana (EKONOMI DAN BISNIS DIGITAL, 2023)
Performance Appraisal is important for an organization and human resources who are members of the organization. Variables in performance appraisal can affect employee performance. This study aims to assess the variables in evaluating the performance of employees of the Investment and One-Stop Service Office whether or not it is appropriate to use it to assess employee performance.This study is based on the Systematic Literature Review (SLR) which includes 35 articles published from 2020 to 2023. The study shows that employee performance is influenced by motivation, discipline, appreciation, innovation, loyalty. Variables in performance appraisal consist of high enthusiasm, service attitude, high commitment, not currently undergoing employee disciplinary punishment, being responsible for each task given in accordance with the field, innovative, proactive related to the implementation of tasks, functions and efforts to improve service quality, discipline time, orderly dress code, orderly employee code of ethics and consistency with the enforcement of disciplinary rules and code of ethics, for Civil Servants with performance appraisal A. There are several assessment criteria that have not been included in existing research.